Effect of Curcuma longa Extract as Adjuvant Therapy on IL-6 Serum Levels in Leprosy Type 1 Reaction Patients - Putri, Syifa Nurisma; Mundhofir, Farmaditya Eka Putra; Yuniati, Renni; Wijayahadi, Noor; Nindita, Yora (Jurnal Health Sains, 2024)
Type 1 leprosy reaction / Reversal reaction (RR) is an inflammatory episode in existing leprosy lesions and aggravates the pain rate. Long-term therapy with steroids causes a variety of side effects, so an adjuvant therapy alternative is needed to alleviate steroid use. Curcuma longa rhizome extract has become an anti-inflammatory therapy choice in various previous inflammatory diseases. This study aims to determine the anti-inflammatory effect of Curcuma longa rhizome extract as an adjuvant therapy for reversal reaction patients by analyzing serum levels of IL-6 as a marker of inflammation. The pre and post-test randomized single-blinded controlled trial was conducted on two groups, namely control (RR patients with steroid therapy & placebo) and treatment (steroid therapy & Curcuma longa rhizome extract 1 gram/day). IL-6 serum levels were analyzed from sampling before and after the intervention for one month. The serum levels of IL-6 post-test in the control group were significantly higher than those of the pre-test. The treatment group showed lower serum levels of IL-6 post-test compared to pre-test, although there was no significant difference. Curcuma longa rhizome extract 1 gram/day for one month as adjuvant therapy for patients with type 1 leprosy reaction did not significantly reduce serum IL-6 levels.